Discovery of novel N-phenyl 1, 4-dihydropyridines with a dual mode of antimycobacterial activity. Issue 24 (15th December 2016) - Lentz, Fabian; Hemmer, Marc; Reiling, Norbert; Hilgeroth, Andreas
Graphical abstract: Abstract: There is an urgent need for novel drugs for the treatment of tuberculosis (TB) due to the increasing prevalence of antibiotic resistance among Mycobacterium tuberculosis (Mtb) strains against first-line and second-line therapeutics. We developed novel N- phenyl 1, 4-dihydropyridines as potential antituberculotic agents. The observed activity depends on the substitution patterns of the aromatic residues. N- unsubstituted 1, 4-dihydropyridines are known inhibitors of the cancer-relevant transmembrane efflux pump ABCB1. Based on the similarity of ABCB1 amino acids sequences relevant to 1, 4-dihydropyridine binding and the MTb efflux pump Rv0194, we determined ABCB1-inhibitory properties of our compounds in a cell line model. We identified one compound, which substantially increased the activity of two antituberculotic drugs which are substrates of ABCB1. The data indicate that our N- phenyl 1, 4-dihydropyridines represent a novel compound class which improves the efficacy of anti-TB drugs by interfering with transmembrane efflux pumps in Mtb.